a)\(\sqrt{x+1}-\sqrt{x-2}=1\)
Đk:\(x\ge2\)
\(pt\Leftrightarrow\left(\sqrt{x+1}-2\right)-\left(\sqrt{x-2}-1\right)=0\)
\(\Leftrightarrow\dfrac{x+1-4}{\sqrt{x+1}+2}-\dfrac{x-2-1}{\sqrt{x-2}+1}=0\)
\(\Leftrightarrow\dfrac{x-3}{\sqrt{x+1}+2}-\dfrac{x-3}{\sqrt{x-2}+1}=0\)
\(\Leftrightarrow\left(x-3\right)\left(\dfrac{1}{\sqrt{x+1}+2}-\dfrac{1}{\sqrt{x-2}+1}\right)=0\)
Dễ thấy:\(\dfrac{1}{\sqrt{x+1}+2}-\dfrac{1}{\sqrt{x-2}+1}< 0\)
Nên \(x-3=0\Rightarrow x=3\)
b)\(\sqrt{x-1}-\sqrt{5x-1}=\sqrt{3x-2}\)
Đk:\(x\ge1\)
\(pt\Leftrightarrow\sqrt{x-1}=\sqrt{5x-1}+\sqrt{3x-2}\)
\(\Leftrightarrow x-1=5x-1+3x-2+2\sqrt{\left(5x-1\right)\left(3x-2\right)}\)
\(\Leftrightarrow2-7x=2\sqrt{\left(5x-1\right)\left(3x-2\right)}\)
\(\Leftrightarrow49x^2-28x+4=4\left(5x-1\right)\left(3x-2\right)\)
\(\Leftrightarrow49x^2-28x+4=60x^2-52x+8\)
\(\Leftrightarrow-11x^2+24x-4=0\Leftrightarrow\left(2-x\right)\left(11x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{2}{11}\end{matrix}\right.\) (loại hết)
c)\(\sqrt{x}-\sqrt{x+1}-\sqrt{x+4}+\sqrt{x+9}=0\)
Đk:\(x\ge0\)
\(pt\Leftrightarrow\sqrt{x}-\left(\sqrt{x+1}+1\right)-\left(\sqrt{x+4}+2\right)+\left(\sqrt{x+9}-3\right)=0\)
\(\Leftrightarrow\sqrt{x}-\dfrac{x+1-1}{\sqrt{x+1}+1}-\dfrac{x+4-4}{\sqrt{x+4}+2}+\dfrac{x+9-9}{\sqrt{x+9}-3}=0\)
\(\Leftrightarrow\sqrt{x}-\dfrac{x}{\sqrt{x+1}+1}-\dfrac{x}{\sqrt{x+4}+2}+\dfrac{x}{\sqrt{x+9}-3}=0\)
\(\Leftrightarrow x\left(\dfrac{1}{\sqrt{x}}-\dfrac{1}{\sqrt{x+1}+1}-\dfrac{1}{\sqrt{x+4}+2}+\dfrac{1}{\sqrt{x+9}-3}\right)=0\)
Dễ thấy:\(\dfrac{1}{\sqrt{x}}-\dfrac{1}{\sqrt{x+1}+1}-\dfrac{1}{\sqrt{x+4}+2}+\dfrac{1}{\sqrt{x+9}-3}>0\)
Nên \(x=0\)